Cuidados de enfermería y su relación con la calidad de vida en adultos mayores con hipertensión arterial del centro gerontológico "adultos mayores en actividad" octubre 2019- marzo 2020 Montalvo, Los Ríos - Aguiar Gaibor, Jhomira Lisbeth (2020)
Nursing care is important to achieve adequate prevention and effective care of high blood pressure. The job of nurses is to provide self-care and information needed to achieve lifestyle goals; since noncommunicable diseases (high blood pressure) are the leading causes of morbidity and mortality nationwide. The main objective of our research is to determine how nursing care influences the quality of life of older adults with high blood pressure at the Centro Gerontológico "Adultos mayores en actividad" in Montalvo canton, Los Ríos Province. The hypothetical-deductive method was applied, the type of research used, field, exploratory, transversal, with a sample of 40 older adults. The most important results show that the older adults are in good physical and emotional condition, and also that 97% have a good relationship with the health personnel. This indicates that the patients feel very comfortable with their environment, while 3% do not feel comfortable with the existing staff. As a conclusion we have that the nursing staff, performs very well its work, maintaining a good relationship nurse - patient, and performs a proper clinical control.